Pengaruh karakteristik informasi akuntansi manajemen terhadap kinerja manajerial pada PT. Bank Sulutgo - Missah, Lusia N; Ilat, Ventje; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2019)
Increasing business competition requires companies to make the most of existing capabilities to excel in competition. This can be achieved by increasing managerial performance. In its operations, PT Bank SulutGo really needs and relies on every internal and external information. This study aims to determine the effect of the characteristics of management accounting information of managerial performance at PT Bank SulutGo. This research uses quantitative research methods. For data analisys methods using multiple linear regression analisys. The results showed that: (1) broadscope variable influences managerial performance; (2) the timeliness variable influences managerial performance; (3) the aggregation variable influences managerial performance; and (4) variable integration has no effect on managerial performance.